Strategi Inovasi Kemasan (Packaging) untuk Meningkatkan Pemasaran Produk Olahan Madu - Diyan Larasati; Febri Anika Lutfianti; Salwa Melinda; Khalimatus Sadiyyah; Diah Ayu Nur Fitriani; Fitri Yulianti (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
This community service activity was carried out on Saturday, September 23 2023, in Kutosari Village, Gringsing District, Batang Regency, precisely at the house of the head of the Kutosari Village honey bee farmer.  This training was attended by 30 honey bee farmers from Kutosari Village.  Core Stage At this stage, introductory material is presented on the benefits of packaging, briefing on the importance of packaging for the product.  The instructor conveys a good technical packaging process.  This stage is a packaging process, namely by practicing packaging, participants are divided into 6 groups, each group works and is creative through the recommended application in making brand designs for each product, and making honey hampers, honey bouquets and honey delivery in beautiful baskets.  Final Stage At this stage the packaging is complete, showing the creativity of each group by providing explanations and reasons regarding the packaging and brand design that has been created.  The training that has been carried out should not stop, but be followed up with independent activities again so that honey bee farmers become more skilled in improving the marketing of processed honey products.